Do not lean too far – evidence from the first decade. (26th November 2007) - Towill, Denis R.; Christopher, Martin
Recent years have seen an increasing focus, both in business and academia, on the totality of supply chains. There is a recognition that supply chain management can have a significant impact on both costs and revenues and that there is a direct correlation between the way that supply chains are designed and shareholder value. Our paper explores one of the major themes that has attracted considerable discussion over the last decade. This is the debate on the appropriateness of the so-called 'lean' and 'agile' paradigms in different business and market environments. It concludes that for most companies, the requirement is for the design and management of multiple pipelines to reflect the diversity of the markets that they serve.